Motivations to Visit Events/Festivals: An Exploratory Investigation - Shanka, Tekle; Alamiyo, Gladys (Australian and New Zealand Marketing Academy, 2012)
Events and Festivals have been recognized by various studies as an important motivator of tourism. Past research show that events/festivals can bring positive benefits such as economic, social and community togetherness to their host community. In addition, events/festivals have the ability to create memorable experience for visitors, dampen negative images regarding host community, and create activities to motivate travellers. The current study assesses motivators to attend an event or a festival in a Western Australian (WA) setting. A convenience sample of 325 students from a large WA university completed a structured questionnaire about their motivations to attend an event/festival in the past 12 months. Findings indicate that the 15 motivational factors significantly discriminate between five clusters of participants.